Tingkat Pengetahuan Ibu Dengan Konsumsi Kalsium Dan Status Gizi Anak SDN 2 Ampenan Kecamatan Sekarbela - Febriyana Ramdhani Utami; Aladhiana Cahyaningrum; Susilo Wirawan (Jurnal Gizi Prima (Prime Nutrition Journal), 2019)
This Study to identify the relationship with the mother's knowledge level of calcium intake and nutritional status of SDN 2 Ampenan District of Sekarbela. The National Food Widya Karya X (WKNPG X) 2012 has been issued AKG 2012, which makromineral adequacy of calcium of 1000 mg per day for children aged 7-9 years, and 1200 mg for children aged 10-12 years. Average consumption of calcium per day by 30% of Indonesia's population, or 300 mg per day, under the instigation WKNPG 2012 that recommended. Calcium needs can be met through a variety of foods, such as meat, fish, milk, vegetables, and fruit. The study design uses observational study, based on the terms of the time of this study using cross-sectional approach,  the objective of this study was the students of SDN 2 Ampenan aged 7-9 years and 10-15 years and ibu-ibu of students of SDN 2 Ampenan. Samples were obtained as many as 38 people, which will be measured weight and height, then 2x24 hour recall interviews were conducted, but it is also done interviews and FFQ questionnaires to the respondents. To determine which variables are examined using analysis with SPSS 16.0 for Windows with Spearman Rank test with a significance level of 0.05. the result shows of the 38 samples studied most (97.36%) aged 10-15 years, and the remainder (2.6%) aged 7-9 years, the nutritional status of a sample of normal category 76.32%, and 100% levels of calcium intake deficits, as well as the level of knowledge of respondents 76.32% lower.  Then, the conclusion is there is no relationship with the level of knowledge of the nutritional status, there was no association between calcium intake and nutritional status, and there is a correlation between the level of knowledge with calcium intake.